Adequacy of good practice in two FAST FOOD restaurantes in municipality of São Paulo, SP, Brazil - Weber, Marcia; Milan, Aline; de Paula Silva, Joyce; Marques Nogueira, Natália; da Silva, Pamela (Brazilian Journal of Global Health, 2021)
OBJETIVO: Identificar a adequação das boas práticas em dois restaurantes de duas franquias de fast-food tipo americano no município de São Paulo, SP, Brasil. MÉTODOS: Utilizou-se em cada restaurante, identificados como A e B, um checklist adaptado da legislação sanitária, cujos itens foram agrupados em 5 blocos: Edificação e instalação, Equipamentos, móveis e utensílios, Manipuladores, Produção e transporte do alimento, e Documentação. A classificação dos restaurantes foi baseada na legislação sanitária: grupo 1, entre 75 e 100% de conformidades; grupo 2, entre 51 e 74% de conformidades; e grupo 3, de 0 a 50% de conformidades. Foi realizada a classificação geral dos restaurantes e por bloco de itens. RESULTADOS: O restaurante A foi classificado no grupo 2 e o B, no grupo 1. A maioria das não conformidades foi observada nos blocos Documentação, Produção e transporte, e Manipuladores para ambos os restaurantes; e Edificação e instalação para o restaurante A. CONCLUSÂO: O restaurante B apresentou maior percentual de conformidades que o restaurante A, e a classificação foi grupo 1 e 2, respectivamente. Independente da classificação, ambos apresentaram não conformidades relevantes à segurança do alimento produzido. A partir disso, sugere-se aplicação de um plano de ação para adequação à legislação vigente, garantindo qualidade aos alimentos e saúde aos consumidores. DESCRITORES: Checklist, Boas práticas de fabricação, Segurança alimentar; Restaurantes, Higiene alimentar. ABSTRACT OBJECTIVE: To identify the adequacy of good practices in two restaurants of two American fast-food franchises in the city of São Paulo, SP, Brazil. METHODS: A checklist adapted from the health legislation was used in each restaurant, identified as A and B, whose items were grouped into 5 blocks: Building and installation, Equipment, furniture and utensils, Handlers, Food production and transportation, and Documentation. The classification of the restaurants was based on the sanitary legislation: group 1, between 75 and 100% of conformities; group 2, between 51 and 74% of conformities; and group 3, from 0 to 50% of conformities. The general classification of the restaurants and by block of items was carried out. RESULTS:Restaurant A was classified in group 2 and B in group 1. Most of the non-conformities were observed in the blocks Documentation, Production and transport, and Manipulators for both restaurants; and Building and installation for restaurant A. CONCLUSION: Restaurant B had a higher percentage of conformities than restaurant A, and the classification was group 1 and 2, respectively. Regardless of the classification, both presented non-conformities relevant to the safety of the food produced. Based on that, it is suggested to apply an action plan to adapt to the current legislation, guaranteeing quality to food and health to consumers. DESCRIPTORS: Checklist, Good manufacturing practices, Food safety; Restaurants, Food hygiene.